2006
DOI: 10.1097/01.mlr.0000233678.80203.c1
|View full text |Cite|
|
Sign up to set email alerts
|

Internet-Based Chronic Disease Self-Management

Abstract: The Internet-based CDSMP proved effective in improving health statutes by 1 year and is a viable alternative to the small-group Chronic Disease Self Management Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
382
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(395 citation statements)
references
References 25 publications
(23 reference statements)
10
382
2
1
Order By: Relevance
“…Self-efficacy has consistently emerged as a mediator of intervention effects on health outcomes (e.g., psychological well-being, function/disability, quality of life) in a variety of populations (Elavsky et al, 2005;Lorig et al, 2006;McAuley et al, 2007;McAuley et al, 2008). In particular, the relationship between stress and self-efficacy has been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy has consistently emerged as a mediator of intervention effects on health outcomes (e.g., psychological well-being, function/disability, quality of life) in a variety of populations (Elavsky et al, 2005;Lorig et al, 2006;McAuley et al, 2007;McAuley et al, 2008). In particular, the relationship between stress and self-efficacy has been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these known benefits and expert recommendations, comprehensive programs have achieved limited translation into routine clinical practice. Many prominent diabetes self-management programs and most IHCAs do not even attempt to send reports to patients' providers [12], and to our knowledge, there are no published reports on efforts to enhance such integration.…”
Section: Introductionmentioning
confidence: 99%
“…Bodenheimer describes self-management and self-management support as collaborative, with healthcare professionals as experts on disease and patients as experts on their lives [11]. Lorig et al recently demonstrated that a chronic disease self-management support program could be successfully delivered over the Web [12,13]. Self-management support appears to be particularly effective when it is systematically integrated into clinical care [14,15].…”
Section: Introductionmentioning
confidence: 99%